Resistance pattern of enterobacteriaceae isolates from urinary tract infections to selected quinolones in Yaoundé - Lyonga, Emilia Enjema (Pan Afr Med J, 2015)
INTRODUCTION: It is estimated that 150 million urinary tract infections (UTIs) occur yearly worldwide, resulting in more than 6 billion dollar in direct healthcare cost. The etiology of UTIs is predictable, with Escherichia coli, an Enterobacteriaceae being the principal pathogen. Quinolones are usually the drug of choice. In this study, we report the resistance pattern of Enterobacteriaceae isolates from UTIs to quinolones among in-patients and out-patients at the Yaoundé Reference Hospital in Cameroon. METHODS: A cross-sectional descriptive study was carried out for a ten-month period. Consecutive clean-catch mid-stream urine samples were collected from 207 in and out-patients. Identification was done using the Api 20E, and susceptibility testing using the Kirby Bauer's disc diffusion method and the MIC was done using the E-test. RESULTS: Out of the 207 isolates, 58(28.0%) were found to be resistant to all the quinolones used in the study. The resistances observed by species were in the order: Enterobacter 4(30.8%); Klebsiella 19(29.7%); Escherichia 25 (29.4%); Proteus 2(11.8%); Serratia 4(25.0%). Quinolone resistance for Escherichia was 42.9% for In-Patients (IP) and 16.3% for Out-Patient (OP) (P-value = 0.006); Klebsiella 35.9% for IP and 20% for OP; Proteus 11.1% for IP and 12.5% for OP; Serratia 18.2% for IP and 40% for OP; Enterobacter 22.2 for IP and 50% for OP. CONCLUSION: High resistance rates to quinolones were observed not only for in-patients but also for out-patients with urinary tract enterobacterial infections. These findings demonstrate the importance of antibiotics susceptibility testing in improving quinolones prescription practices in Cameroon.